Analysis Of Constraints Of Tourism Institutions An Applied Study Of A Sample Of Hotels And Motels In Erbil In 2020 - Amer Abdulla Majid (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The development of tourism institutions, especially hotels and motels in the Kurdistan region of Iraq, aims at the flow of revenues to the region, as well as providing job opportunities for youth in these institutions, especially for graduates of tourism departments in colleges and universities. But there are internal and external obstacles to the tourism institutions to achieve these goals. The research reached a number of conclusions, including: Hotels and motels depend mainly on the experience of the owner, which is a hindrance to the development of the hotel or motel, by (120.3). The political situation in the region is an obstacle to the number of hotel and motel guests, especially in the central and southern governorates, and by (129.47%). In addition, the investment process does not encourage the expansion and development of hotels, motels and tourist villages, and by (127.53%). Administrative and security obstacles negatively affected the number of hotel guests, motels and tourist villages by (136.7%). Raise taxes by the provincial government, negatively affected hotels, motels and tourist villages, and by (143.97%). al crisis in the region, negatively affected the activity of hotels, motels and tourist villages, and by (142.03%). The research reached a number of proposals, including: The responsibility of the Tourism Authority in the Kurdistan Region is to deal with the long administrative routine and the duplication of governmental procedures in government institutions, especially for private tourism establishments such as hotels, motels, tourist villages, restaurants, etc. ease the administrative and security obstacles to the flow of tourists and increase the duration of their stay in the Kurdistan Region. 3- work to reduce taxes on private tourism institutions, and achieve tax justice among these tourism institutions. The Tourism Authority shall have the necessary support and facilities for the private tourist institutions in order to increase tourism investments in the Kurdistan Region, especially in light of the current financial crisis.